Pengembangan Instrumen Uji Perlambatan Kendaraan Berdasarkan Gerak Lurus Berubah Beraturan pada Metode Road Test - Wibowo, Muhammad Riski Septiana; Hakim, M. Iman Nur; Shofiah, Siti; Risqi, Muhammad Isro; Firdaus, Denisya Haddad (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The braking system was a crucial component in ensuring the safety of motor vehicles on the road. Brake failures, such as brake fade or total malfunction, could result in fatal accidents. Therefore, an accurate and realistic testing method was necessary to measure the effectiveness of a vehicle’s braking system. This study aimed to develop a deceleration measuring device based on GPS, which could be used in road test methods. The device was designed using an ESP32 microcontroller combined with a BN-220 GPS module, RTC real-time clock sensor, 16x2 LCD, thermal printer, and microSD storage media. Testing was conducted on a Mitsubishi L300 vehicle at the Depok Beach runway in Yogyakarta, with initial speed variations ranging from 10 to 80 km/h. Calibration results showed that the device had an accuracy of 99.64% with an average error of 0.36%. Meanwhile, the test results recorded deceleration values ranging from 0.74 to 3.26 m/s², depending on the initial speed and braking conditions. Based on these findings, the developed device proved to be accurate and feasible as an alternative method for field testing of braking systems.